Vamos a la Playa vs. Standing at the Gates: Beaches in Bulgaria. Issue 4 (4th July 2018) - Egbert, Henrik; Todorov, Aleksandar B.
ABSTRACT: Beaches at the Bulgarian Black Sea coast were public and club goods until the mid-1990s. By that time the Bulgarian government had granted private investors temporary property rights by providing concessions. Consequently, more beaches show characteristics of club goods nowadays. On a national level, the process can be considered as a reallocation of public resources, thus affecting the well-being of many. This paper focuses on three aspects of this process and contributes to the ongoing discussion of how to handle public resources by addressing the case of beaches in Bulgaria. We first describe the process as observed for beaches in order to provide an analytical basis for further research. Stakeholders and their interests are then identified. The paper proceeds by pointing at conflicts between the different types of shareholders.